“Dark patterns” in online services: a motivating study and agenda for future research - Julian Runge; Daniel Wentzel; Ji Young Huh; Allison Chaney (Marketing Letters, 2022)
Some companies offering online services employ tactics that make it hard for customers to quit their accounts. These tactics are commonly referred to as "dark patterns" and may include hiding the cancelation procedure, asking customers to go through an excessive number of steps to complete the cancelation, or simply not letting customers quit their accounts straight away. Arguably, dark patterns are the result of misaligned incentives between companies and customers as companies can still benefit from their customers' data even if they no longer use the companies' services. Against this background, the authors conduct an observational survey of the state of current market practice and call for future research that enhances our understanding of dark patterns, their organizational antecedents, customers' psychological responses to these tactics, and the wider consequences of dark patterns for firms and markets.
Keywords: 380; Dark patterns; Online services; Platform economy; Privacy